The importance of using assistive technology in the education of the deaf (Research, Society and Development, 2021)
Through qualitative bibliographic research, this paper aims to present the importance of ICTs (Information and Communication Technologies) in the learning process of deaf students, as well as to establish a parallel between them and distance education through Virtual Learning Environments (AVA), as a complementary tool to reduce segregation and facilitate the acquisition of knowledge and communication of primary school students. The deaf student has the right to education guaranteed by a series of laws and decrees, including in regular schools. This inclusion, however, does not occur satisfactorily, due to innumerable factors, but, mainly, the lack of preparation of the agents involved and the lack of knowledge of the needs of the deaf and the tools he has are determining factors in the full educational development of students with disabilities. disability, especially deafness, the focus of this study. In this context, Assistive Technologies (AT), through ICT’s, appear as important methodologies that are inserted in the educational environment offering a range of tools that provide autonomy, independence and quality of life in the process of including deaf students in regular education. Despite many problems on the subject, it can be concluded that AT is an area of effective knowledge for improving communication and learning for deaf students, also facilitating relationships between themselves and with listeners, hence the importance of extending their use for educational processes.